Upaya Pencegahan Penularan Covid-19 di Pondok Pesantren Lirboyo Kota Kediri - Qomarul Huda, Mohammad; Abdul Mujib; Mubaidi Sulaeman (Jurnal SOLMA, 2022)
Background: Islamic educational institutions that are managed by a group of people, always require the cooperation and intervention of other parties as the main buffer. This service aims to bring order to the implementation of health protocols in the Lirboyo Islamic Boarding School environment during the COVID-19 pandemic. Method: the approach used is Asset Based Community Development. This approach emphasizes the inventory of assets contained in community groups that are seen as supporting community empowerment activities. Results: Direct education has contributed to increasing students' understanding of the importance of implementing health protocols during the COVID-19 pandemic. Conclusion: Awareness of the importance of health in the Lirboyo Islamic boarding school environment has been carried out well.